2007
DOI: 10.1007/s00520-006-0207-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a cancer diagnosis on the health behaviors of cancer survivors and their family and friends

Abstract: Goals The aim of this study was to examine the effect of a cancer diagnosis on the health behaviors of cancer survivors and their family and friends, and to determine whether a cancer diagnosis could be a teachable moment for intervention. Materials and methods This was a cross-sectional study of the health behaviors of individuals taking part in a cancer fundraising event. The questionnaire was completed by 657 participants. Main results Participants were 81.4% women, had a mean age of 46 years, and comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
127
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 41 publications
10
127
0
5
Order By: Relevance
“…Older survivors had better diet quality than did younger survivors. Such an age effect was previously reported in cancer survivors (25)(26)(27)(28)and may partly reflect better dietary habits in older than in younger generations (i.e., cohort effect) or overall better health in survivors who survived longer (i.e., survivor bias) (29). Consistent with previous findings (25,28,(30)(31)(32), diet quality for male survivors and survivors with low educational attainment, who currently smoke, or who are obese was poor and these individuals may be viable targets for dietary interventions.…”
Section: Discussionsupporting
confidence: 51%
“…Older survivors had better diet quality than did younger survivors. Such an age effect was previously reported in cancer survivors (25)(26)(27)(28)and may partly reflect better dietary habits in older than in younger generations (i.e., cohort effect) or overall better health in survivors who survived longer (i.e., survivor bias) (29). Consistent with previous findings (25,28,(30)(31)(32), diet quality for male survivors and survivors with low educational attainment, who currently smoke, or who are obese was poor and these individuals may be viable targets for dietary interventions.…”
Section: Discussionsupporting
confidence: 51%
“…Studies from other countries also pointed out similar findings (Humpel et al, 2007;Son et al, 2011).…”
Section: Discussionsupporting
confidence: 66%
“…With the exception of respondents in the pre-treatment phase, respondents with crc reported making more lifestyle changes than did cancer-free controls. It could be that a cancer diagnosis provides a "teachable moment" for lifestyle change, as has been suggested by other studies 2,12,59 . When considering the 6 stages of change described by the ttm 17 , a cancer diagnosis may work as a cue to move some people from the "contemplative stage" to the subsequent "preparation" stage.…”
Section: Timing Of Lifestyle Resourcesmentioning
confidence: 77%
“…That finding was unexpected because previous studies had suggested that the timing of interventions and support might be important 2,12,58 . Furthermore, our results suggest that that the proportion of people at the preparation stage of the ttm may have been lower in the pre-treatment group than in the groups that had begun or completed treatment.…”
Section: Timing Of Lifestyle Resourcesmentioning
confidence: 85%
See 1 more Smart Citation